Clinical Spectrum of LIG4 Deficiency Is Broadened with Severe Dysmaturity, Primordial Dwarfism, and Neurological Abnormalities. Issue 12 (18th September 2013) - IJspeert, Hanna; Warris, Adilia; van der, Michiel; Reisli, Ismail; Keles, Sevgi; Chishimba, Sandra; van, Jacques J.M.; van, Dik C.; van der, Mirjam
<x xml:space="preserve">Abstract</x> In a patient with severe dysmaturity, primordial dwarfism, and neurological abnormalities, we identified two heterozygous mutations in LIG4. The p.S205LfsX29 mutant was only expressed in the cytoplasm and therefore represented a null mutation. The second mutant (p.K635RfsX10) was expressed in the nucleus, but lacks an important domain necessary for its stability, implying that this mutant has probably very low residual activity. This study shows that the clinical spectrum of LIG4 deficiency is broadened with a new clinical phenotype. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>